Sectoral systems of innovation concepts, issues and analyses of six major sectors in Europe - Malerba, Franco 1950- (Cambridge University Press, 2004)
Innovation and technological change show different rates, types and trajectories depending on the sector in which they take place. Agents and institutions of a sector all exert a major influence on innovation. With contributions from nineteen experts in their field, this book proposes the framework of the 'sectoral systems of innovation' to analyse the innovation process, the factors affecting innovation, the relationship between innovation and industry dynamics, the changing boundaries and transformation of sectors, and the determinants of the international performance of firms and countries in different sectors. Innovation in a sector is considered to be affected by three groups of variables: knowledge and technologies; actors and networks; and institutions. In addition to the general framework, this book examines innovation in six major sectors in Europe including pharmaceuticals and biotechnology, telecommunications equipment and services, chemicals, software, machine tools and services
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Technological innovations / Economic aspects / Europe / Case studies; Innovation; Branche; Technischer Fortschritt; Europa; Fallstudiensammlung